(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Swami Dayananda was the founder of Arya Samaj. He was a great preacher of Vedic literature, a dynamic social reformer and a profound philosopher. He sacrificed the luxuries and comforts of life for the emancipation of society. He envisioned a society based on equity and mutual respect.